2022
DOI: 10.4049/jimmunol.2100695
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products (AGEs) Inhibit Macrophage Efferocytosis of Apoptotic β Cells through Binding to the Receptor for AGEs

Abstract: Pancreatic β cell apoptosis is important in the pathogenesis of type 2 diabetes mellitus (T2DM). Generally, apoptotic β cells are phagocytosed by macrophages in a process known as “efferocytosis.” Efferocytosis is critical to the resolution of inflammation and is impaired in T2DM. Advanced glycation end products (AGEs), which are increased in T2DM, are known to suppress phagocytosis function in macrophages. In this study, we found that AGEs inhibited efferocytosis of apoptotic β cells by primary peritoneal mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…AGEs can directly produce deleterious effects or exert their damaging effects through the receptors of AGEs (RAGEs). Both MGO and AGEs can induce the most deleterious consequences directly or by stimulating RAGE signaling [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…AGEs can directly produce deleterious effects or exert their damaging effects through the receptors of AGEs (RAGEs). Both MGO and AGEs can induce the most deleterious consequences directly or by stimulating RAGE signaling [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to macrophage polarization, in this study, we also assessed the efferocytosis of macrophages. Efferocytosis described the process by which the apoptotic cells were engulfed and digested by phagocytes, especially macrophages, and without efferocytosis, the apoptotic cells underwent necrosis and released harmful cell products, resulting in an excessive inflammatory response [28,29]. The growth arrest specific gene 6 (Gas6)/protein S (ProS)-TAM system consisted of two vitamin K-dependent ligands (Gas6, ProS) and three receptor tyrosine kinases (TYRO3 protein tyrosine kinase [Tyro3], AXL receptor tyrosine kinase [Axl], and c-mer proto-oncogene tyrosine kinase [MERTK], which were collectively referred to as TAM receptors) that participated in efferocytosis [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies showed reduced phagocytosis of apoptotic neutrophils by macrophages in RAGE-deficient mice [109]. Elevated AGEs in type 2 diabetes inhibit macrophage phagocytosis by disrupting RAC-1 activity and cytoskeletal rearrangement through RAGE/Rho kinase signaling in macrophages [110].…”
Section: Impaired Efferocytosis and Expression Of Aim2 Inflammasomes ...mentioning
confidence: 98%